학교보안관의 직무수행 척도 개발 - 김경식(Kyong-Sik Kim); 김은정(Eun-Jung Kim) (한국콘텐츠학회 논문지, 12(7), 2012)
This study is aimed at developing a tool to measuring school police's job performance, and verifying its credibility and validity. This study collected the sample to 250 subjects using a significance collection method to parents of elementary schools school police work. But excluding dishonestly responding data, this used total 210 people for the final analysis. This study executed experts' meeting, exploratory and confirmatory factor analysis, and item analysis to verify reliability, and verification of internal consistency and reliability. This study extracted and confirmed 7 factors for specialization, attitude, program, prevention activity of school violence, effect, basic duty, teaching for school time and home time, and correlation with related people. Through the above research approach and procedure, this study arrived at the following conclusion. First, validity to school police's job performance and measurement tool to job performance is very high. That is, school police's job performance was explored and confirmed through correlation with specialization, attitude, program, prevention activity of school violence, effect, basic job, teaching for school time and home time, and related people, and of them, explanation of attitude is the highest. Second, reliability to the measurement scale for school police's job performance is very high. That is, school police's job performance has high correlation between items, sub-factors, and total scores, and reliability of internal consistency, Cronbach's ${α}$ value, is over .708. Putting them together, measurement scale for school police's job performance is a questionnaire sheet with very high level of validity and reliability. 이 연구는 학교보안관의 직무수행 측정도구를 개발하여 타당도와 신뢰도를 검증하는데 목적이 있다. 이 연구는 2011년 서울소재 학교보안관이 근무하고 있는 초등학교 학부모들을 대상으로 유의표집법을 활용하여 250명의 연구대상을 표집 하였다. 그러나 응답이 불성실한 자료를 제외하고 최종분석에 사용된 사례수는 총 210명이었다. 학교보안관의 직무수행 측정도구는 문헌고찰, 개념적 정의 및 설문지 초안 작성, 전문가 회의, 예비검사 및 본 조사, 설문지의 타당도 및 신뢰도 검증 등의 과정을 거처 개발되었다. 통계처리는 SPSSWIN 18.0을 활용하여 탐색적 요인분석, 확인적 요인분석, 신뢰도분석, 상관분석 등을 실시하였다. 이상과 같은 연구방법 및 절차를 통하여 이 연구에서는 다음과 같은 결론을 도출하였다. 첫째, 학교보안관의 직무수행 측정도구에 대한 타당도는 매우 높다. 즉, 학교보안관의 직무수행은 전문성, 태도, 프로그램, 학교폭력예방 활동, 효과, 기본 직무, 등하교지도와 관계자연계성으로 탐색 확인되었으며, 태도의 설명력이 가장 높다. 둘째, 학교보안관의 직무수행 측정도구에 대한 신뢰도는 매우 높다. 즉, 학교보안관의 직무수행은 문항과 영역간, 문항과 총점간 상관정도가 높으며, 내적일관성 신뢰도인 Cronbach's ${α}$값이 .708이상이다. 종합해 보면, 학교보안관의 직무수행 측정도구는 타당도 및 신뢰도가 높은 설문지임을 알 수 있다.